THE SYMBOLISM AND ITS FEATURES IN UZBEK AND ENGLISH LITERATURE (Scientific journal of the Fergana State University, 2023)
The article studies the interpretations of the universe and man by symbolismsin Uzbek national style, characteristic features of using them in Uzbek and English novels.